The significance of large sediment supply, active tectonism, and eustasy on margin sequence development: Late Quaternary stratigraphy and evolution of the Ganges-Brahmaputra delta - Goodbred, S. L.; Kuehl, S. A. (Sedimentary Geology, 2000)
Borehole data from the Ganges-Brahmaputra delta system unveil an intriguing Late Quaternary history controlled by immense sediment discharge, tectonics, and eustasy. Sea level first intersected a major portion of the lowstand surface similar to 10,000-11,000 cal yr BP, marking the onset of sediment trapping and delta growth. Despite rapid sea-level rise (>1 cm/yr), sediment load was sufficient to maintain relative shoreline stability during this time. By similar to 7000 cal yr BP, accommodation was quickly infilled with slowed sea-level rise, leading to upstream channel migration and widespread dispersal of sands. This forced coastal progradation along the western delta front where the Ganges was situated, and much of the river's fine-grained discharge bypassed the subaerial delta and formed a prograding deltaic clinoform on the shelf. Concurrently, Brahmaputra sediments were sequestered to an inland tectonic basin, thus starving the adjacent shoreline and leading to transgression along the eastern delta. By similar to 5000 cal yr BP, the two rivers had migated or changed course to discharge along the eastern delta shoreline which began to prograde into what is now the modern river-mouth estuary. Present delta configuration appears to have developed by similar to 3000 cal yr BP. Evolution of the tectonically active Ganges-Brahmaputra (G-B) system reveals important similarities and differences with other deltas. Overall facies succession follows that of basic models, progressing from an alluvial valley to coastal marine delta front to a prograding subaerial delta plain. However, the timing, thickness, and controls of these deposits differ. Immense sediment discharge from the Ganges and Brahmaputra rivers allowed initial delta growth 2000-3000 yr earlier than the global average, despite debouching onto a canyon-incised, high-energy margin. Subsequently, a thick (similar to 50 m) transgressive systems tract was formed during the early Holocene phase of delta aggradation, contrasting with extensive shoreline retreat documented along most margins. Highstand progradation of coastal and shelf sequences ensued by the middle Holocene, but subsiding inland basins also favored accumulation of a thick (to 40 m) highstand sequence in the: lower floodplains. Unlike many other delta systems, subsidence in the subaerial G-B delta is not dominated by compaction, but rather by plate-driven tectonic processes that generate rates up to 4 mm/year. Overall, the huge sediment load, tectonic subsidence, major seismic events, and a nearshore canyon system have led to widespread sediment dispersal and sequence formation across the subaerial delta, shelf, and deep-sea Bengal Fan throughout the Late Quaternary. (C) 2000 Elsevier Science B.V. All rights reserved.
337jeTimes Cited:203Cited References Count:63